Estudio de chorros diesel usando mecánica de fluidos computacional - Agudelo, John; Agudelo, Andrés; Benjumea, Pedro (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
In this work a numerical model for simulating the main sub-processes occurring in a fuel spray was developed using an open-source CFD code. The model was validated by comparing predicted dimethyl ether (DME) spray tip penetrations with experimental data reported in literature and some results obtained from empirical correlations. Once validated, the model was used for evaluating the effect of fuel type, injection pressure and ambient gas pressure on spray tip penetration, Sauter mean diameter (SMD) and evaporated fuel mass. Fuel properties significantly affected the atomization and evaporation processes and in a lesser extent spray fuel penetration. Regarding the injection and ambient gas pressures, the SMD increased with viscosity and surface tension while the evaporation rate increased with fuel volatility. At low ambient gas pressures the evaporation process was highly favored as well as the spray penetration. For both fuels, as injection pressure increased the SMD decreased and the evaporation rate increased.